Colleges and schools-College of Agricultural Sciences and Technology-Industrial Technology 044
The Department of Industrial Arts and Technology at California State University, Fresno is the beneficiary in the donation of $6,000 worth of automotive equipment provided by the Ford Motor Company through the J.H. Sanders Ford agency in Clovis. Leslie Aldrich (right), professor of industrial arts and technology at CSUF, shoes the progress in assembling part of the equipment to J.H. Sanders (left), owner of the Clovis dealership, and Chuck Self (center) service manager for the firm. The Pinto engine and transmission shown will be connected to a dynamometer in a test cell for instructional use in the energy laboratory of the new addition to the University's Industrial Arts Building. The equipment is being assembled by Roberto Mora, a senior at CSUF majoring in industrial arts. Mora is participating in the federally funded work study program, in which students work in a variety of campus jobs and receive funancial aids ar CSU, Fresno, said the equipment donation illustrates the cooperation in higher education involving corporations, local business firms, the state represented by the University, and the federal government in providing financial assistance to students.